Brown adipose Vanin-1 is required for the maintenance of mitochondrial homeostasis and prevents diet-induced metabolic dysfunction - Chen Sun; Jiaqi Liang; Jia Zheng; Shuyu Mao; Siyu Chen; Ainiwaer Aikemu; Chang Liu (Elsevier, 2024)
Background: Energy-dissipating brown adipocytes have significant potential for improving systemic metabolism. Vanin-1, a membrane-bound pantetheinase, is involved in various biological processes in mice. However, its role in BAT mitochondrial function is still unclear. In this study, we aimed to elucidate the impact of Vanin-1 on BAT function and contribution during overnutrition-induced obesity. Methods: Vanin-1 expression was analyzed in different adipose depots in mice. The cellular localization of Vanin-1 was analyzed by confocal microscopy and western blots. Mice lacking Vanin-1 (Vanin-1−/−) were continuously fed either a chow diet or a high-fat diet (HFD) to establish an obesity model. RNA-seq analysis was performed to identify the molecular changes associated with Vanin-1 deficiency during obesity. BAT-specific Vanin-1 overexpression mice were established to determine the effects of Vanin-1 in vivo. Cysteamine treatment was used to examine the effect of enzymatic reaction products of Vanin-1 on BAT mitochondria function in Vanin-1−/− mice. Results: The results indicate that the expression of Vanin-1 is reduced in BAT from both diet-induced and leptin-deficient obese mice. Study on the subcellular location of Vanin-1 shows that it has a mitochondrial localization. Vanin-1 deficiency results in increased adiposity, BAT dysfunction, aberrant mitochondrial structure, and promotes HFD induced-BAT whitening. This is attributed to the impairment of the electron transport chain (ETC) in mitochondria due to Vanin-1 deficiency, resulting in reduced mitochondrial respiration. Overexpression of Vanin-1 significantly enhances energy expenditure and thermogenesis in BAT, renders mice resistant to diet-induced obesity. Furthermore, treatment with cysteamine rescue the mitochondrial dysfunction in Vanin-1−/− mice. Conclusions: Collectively, these findings suggest that Vanin-1 plays a crucial role in promoting mitochondrial respiration to counteract diet-induced obesity, making it a potential therapeutic target for obesity.